Quercetin Nanoparticles- A Promising Approach to Cancer Treatment: A Review: Pharmaceutical Science-Pharmaceutics - Deb, Barsha; Thakur, Nishant (International Journal of Life Science and Pharma Research, 2022)
Quercetin, a naturally occurring polyphenolic element, has rapidly received attention as an anticancer agent. Although quercetin has demonstrated potent medical value, its application as an antitumor drug is limited because of poor solubility, low absorption, and fat metabolism. Nanoparticles are effective and versatile drug delivery devices because they can improve the solubility, pharmacokinetics, bio distribution, and in vivo stability of the free drug. The utilization of Nano-carrier scanning increases the bioavailability of the drug. Quercetin nanoparticles have shown high encapsulation efficiency, stability, sustained release, extended circulation time, improved accumulation at tumor sites, and therapeutic efficacy. This review article aims to estimate the anticancer efficiency of polymeric nanoparticles of quercetin. The majority of research is based on the preclinical anticancer activities of quercetin nanoparticles. MCF cells of breast cancer (BC), A 549 cells of lung cancer, cells of HepG2 liver malignancy, and cells of malignance are the primary targets for possible anticancer activity. Furthermore, combining quercetin with other diagnostic or therapeutic agents in a single Nano carrier has resulted in improvements in tumor detection or treatment. The antitumor outcome of drugs that are used in cancer therapy can also be supported by quercetin nanoparticles by increasing the anti-tumor development or decreasing the systemic toxicity level of the drug. Keywords: , , ,